1997
DOI: 10.1016/s0020-7292(97)00221-x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus and glucose intolerance in a Mexican population

Abstract: The overall prevalence of glucose abnormalities during pregnancy was 16%. GI in this group was associated to macrosomia at the same rate as GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Of the 8 included studies, three were retrospective and information was gathered through data linkage or chart review [15,17,18]. One study was performed in the United States [13], one in Asia [18], two in the Middle East [17], one in Europe [12], two in Latin America [14,16] and one was a multi country study [7,19]. All but one study [12] used venous plasma glucose based on the oral glucose tolerance test to diagnose GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8 included studies, three were retrospective and information was gathered through data linkage or chart review [15,17,18]. One study was performed in the United States [13], one in Asia [18], two in the Middle East [17], one in Europe [12], two in Latin America [14,16] and one was a multi country study [7,19]. All but one study [12] used venous plasma glucose based on the oral glucose tolerance test to diagnose GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Low-risk status requires no glucose testing, but this category is limited to those women meeting all of the following characteristics: age <25 years, normal weight before pregnancy, member of a population with a low prevalence of GD, no known diabetes in first-degree relatives, no history of abnormal glucose tolerance, no history of poor obstetric outcome. Where type 2 DM is common (for example many units in the USA, Saudi Arabia and the Gulf, and certain ethnic minorities), then a total population screen is justified (Forsbach et al, 1997). Universal screening is more sensitive and more practical when a family history of diabetes cannot be obtained reliably (Karcaaltincaba et al, 2009).…”
Section: Testing Programsmentioning
confidence: 99%
“…Subsequent studies demonstrated that a greater proportion of neonates of women who meet or exceed blood glucose thresholds used to define GDM are at increased risk for selected morbidities compared with neonates of mothers whose glucose tolerance test results fall below these thresholds [14][15][16][17][18][19][20][21][22][23][24][25][26]. Importantly, the threshold values for the 50-g, 1-hour glucose screening test and the glucose tolerance test were somewhat arbitrarily selected [27,28].…”
Section: Clinical Correlates Of a Single Elevated Postglucose Testmentioning
confidence: 99%